Antifeedant activity of some Tanacetum species and bioassay guided isolation of the secondary metabolites of Tanacetum cadmeum ssp cadmeum (Compositae) - Susurluk, Hilal; Caliskan, Zerrin; Guerkan, Oktay; Kirmiziguel, Suheyla; Goeren, Nezhun (ELSEVIER SCIENCE BV, 2007)
Antifeedant activities of Tanacetum cadmeuin ssp. cadmeum, Tanacetum parthenium, Tanacetum coryinbosum ssp. cinereum, Tanacetum chiliophyllum var. chiliophyllum, Tanacetum kotschyi and Tanacetum cadyneton ssp. orientale were assessed on Spodoptera littoralis Boisd. (Lep: Noctuidae) third instar larvae. The highest antifeedant activities were found as 62 and 55.05% in the extracts of MeOH with T cadmeum ssp. cadmeum aerial parts, MeOH with T corymbostum ssp. cinereum flowers, respectively. Bioassay guided investigations on Tanacetum cadmetum ssp. cadineum afforded three eudesmanolides; artesin (1), taurin (2), and artemin (3), three germ acranolides; tavulin (4), tanachin (5), and tamirin (6), the coumarin; scopoletin (7), and two flavonol derivatives; tanetin (6-hydroxykaempferol 3,7,4'-trimethylether) (8) and 6-hydroxykaempferol 3,6-dimethylether (9). The structures of the compounds were elucidated by spectral methods, such as IR, UV, H-1 NMR and C-13 NMR (COSY, APT, DEPT, HMQC, HMBC, NOE, X-ray, EIMS, CIMS and HRMS). In this paper, the antifeedant activities of some Tanacetum species and the compounds isolated from T cadmeum ssp. cadmeum are reported. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Spodoptera littoralis; tanacetum; flavonoid; coumarin; sesquiterpene lactones; antifeedant activity; VULGARE; ASTERACEAE; PARTHENIUM; ARGENTEUM; EXTRACT; Agriculture